Interactive Communication Among Mobile Legends Players in Responding to Cyberbullying: A Phenomenological Study: Komunikasi Interaktif para Player Mobile Legends dalam Merespons Tindakan Cyberbullying - Alfarizi, Rachel; Rozaq, Miftahul (Kanal: Jurnal Ilmu Komunikasi, 2025)
This study aims to explore the forms of interactive communication among Mobile Legends players in responding to cyberbullying acts that occur during gameplay. Using a phenomenological approach, in-depth interviews were conducted with eight informants who have been actively playing Mobile Legends over the past six months. The findings indicate that in-game communication is heavily influenced by emotional context, competitive pressure, and individual communication styles. Acts of cyberbullying such as insults, provocation, and verbal harassment are commonly found in chat rooms, both explicitly and implicitly. Players respond to these acts in various ways—some remain silent, others retaliate, and a few attempt to mediate the situation. Personal experience, emotional maturity, and digital awareness play crucial roles in shaping how individuals communicate and respond. This study also highlights the need for digital ethics education and empathetic communication within online gaming communities to help prevent the rise of cyberbullying behavior.